SCHOOLS AS IMPORTANT FACTORS IN THE PREVENTION AND SUPPRESSION OF DRUG ADDICTION WITH YOUNG PEOPLE (Annual of the Faculty of Philosophy in Skopje, 2009)
Socialization, as a process of transferring the norms and values for the preparation of young people for life in society, represents an utmost valuable mechanism for the building and forming of the individual’s character and personality. The most important factors of socialization are the family and ones peers, but you certainly cannot ignore the special role of schools. The schools represent a second home for kids, an institution where the child is educated and brought up, and in situations where the family does not pay enough attention to socialization, the school is expected to fill in the gaps. By this we understand putting an accent on the educational process of schools by teachers, but also the guidance of counselors. Today, in a time of crisis, decaying of moral norms and values, weakening of the family cohesion, a rising percent of socio- pathological behavior, and especially drug addiction, the schools are required to be a factor in the fight against deviant behavior. We especially want to point out the meaning that schools have in the prevention of drug addiction because most drug addicts start abusing drugs at the age of 13 or 14, a period of adolescence and a time at which· the child spends most of the time at school with peers who are mostly from the child’s own class and from this comes the meaning that schools play in the fight against drug addiction.
Keywords: SCHOOL; SOCIALIZATION; STUDENT; YOUTH; DRUG ADDICTION